Does Thrombin Activatable Fibrinolysis Inhibitor (TAFI) Contribute to Impairment of Fibrinolysis in Patients with Preeclampsia and/or Intrauterine Fetal Growth Retardation? - Antovic, J.P.; Hamad, R. Rafik; Antovic, A.; Blombäck, M.; Bremme, K. (Thrombosis and Haemostasis, 2002)
Thrombin Activatable Fibrinolysis Inhibitor (TAFI) is a relatively recently described glycoprotein (MM 55 KDa) that can be converted into its active form by the thrombin/thrombomodulin complex and potentially inhibits fibrinolysis. Since it represents a link between coagulation and fibrinolysis, TAFI can be expected to play a part in various clinical conditions associated with a thrombotic tendency. Preeclampsia (PE) and intrauterine fetal growth retardation (IUFGR) are fairly common complications of pregnancy that are characterized by hemostatic abnormalities. TAFI antigen and its influence on hemostasis was investigated in 46 women with PE and/or IUFGR and in 16 normal pregnancies. We found a significant decrease of TAFI antigen in the patient group. Using the recently described method Overall Hemostatic Potential (OHP) in plasma, we measured clot lysis time (CLT) and overall fibrinolytic potential (OFP). We found that CLT is prolonged and OFP decreased in patients with PE and/or IUFGR. Since OFP did not increase after addition of the specific inhibitor of TAFI (potato tuber carboxypeptidase inhibitor), it seems that TAFI does not contribute to the impairment of fibrinolysis in these patients. Since serum albumin was decreased together with presence of proteinuria and aminotransferases were increased in the patients, it seems that one explanation for the decrease in TAFI could be reduced hepatic synthesis and an increased loss in urine. It can be speculated that this mechanism can prevent more serious thrombotic complications in patients with PE and/or IUFGR.
Keywords: TAFI antigen; preeclampsia; overall fibrinolytic potential in plasma (OFP); clotlysis time